O comportamento de recém -nascidos de risco: adaptação transcultural e utilização clínica da Neonatal Behavioral Observation (NBO) - Marina Aguiar Pires Guimarães (2016)
The Neonatal Behavioral Observation (NBO) system is an easy to apply strategy that recognizes the baby´s behavior and individualities, which facilitates its use in Brazil. As the NBO is focused on promoting parents´ engagement and confidence, as well as the link with the health care team, its use in Brazil can be strategic to improve the quality of care for the newborn, which motivated us to invest in the process of cross-cultural adaptation to the Brazilian Portuguese. The objectives of this study were: to conduct a cross-cultural adaptation of the Neonatal Behavioral Observation (NBO), to investigate its clinical utility to characterize the behavioral pattern of newborns of biological and social risk and to assess the quality of the NBO session as experienced by the mothers. To achieve these objectives were carried out two studies, a methodological one of translation of the NBO system instruments (Recording Form, Recording Guidelines, Summary for Parents and Parent Questionnaire) and another cross-sectional study with the use of the NBO. The methodological study followed international recommendations for cross-cultural adaptation of health care instruments, with authorization for translation from the authors, translation, and back translation, followed by external evaluation that scored the quality of the adaptation, which was tabulated and analyzed quantitatively. The quality of the adaptation of the instruments items, a total of 180, was verified using the index of agreement between raters for conceptual and cultural equivalence. According to the expert panel, the translation of the NBO items was well understood conceptually and culturally appropriate, with 140 (77.77%) presenting rater afreement index concerning the conceptual and cultural equivalences greater than 90%. Items that did not reach adequate levels of agreement were reviewed as suggested by the expert panel. The Brazilian version of the NBO instruments can be used safely since the methodology was rigorous enough to ensure equivalence between the original and translated versions. The study of the clinical utility of NBO was conducted between May and October 2015 at the Casa do Bebê of the Hospital Sofia Feldman with all the mother-child dyads who agreed to participate. A questionnaire was used to characterize the sample followed by the NBO session, with one dyad at time, and at the end, the mothers responded to the Parent Questionnaire. The NBO consist of the observation of 18 behavioral and reflex items, scored on a three-point scale. Descriptive statistics were used to characterize the sample, Mann Whitney test for comparison between groups (term and preterms babies), and Wilcoxon test to compare the knowledge, as perceived by the mothers, before and after the NBO. For all analyzes alpha significance level of 0.05 was adopted. The full term babies had higher median than preterms in the areas Motor and Responsiveness (p = 0.003 and 0.021, respectively), with no significant differences in the autonomic control and organization of states. Regarding the opinion of the mothers, they reported greater knowledge about their babie´s behavior after the observation, median 10, p <0.0001. The results suggest that the NBO, although it is not a test, is helpful to characterize specificities in the behavioral paterns of full term and preterm neonates also being a viable and a pleasant resource to raise mothers awareness about their babies´ behavior.